Peningkatan Kemampuan Guru Membuat Adminstrasi Perencanaan Pembelajaran Berdasarkan Analisis Instrumen Akreditasi Pada Guru di SMA Binaan Kabupaten Sambas Tahun Pelajaran 2018/2019 - -, Eni Dwi Kurniawati (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
This research departs from the lack of teacher ability in making Learning Planning Administration (APP) that matches the instrument of acridiation in 2017. It was discovered when carrying out coaching tasks to teachers in target schools. There are still many teachers who do not understand what it takes to create an APP. Therefore, this study aims to: (1) improve the ability of teachers in making APP according to the instrument of akriditasi; and (2) improved teacher ability to make APP according to acrydition instrument. The research method used is School Action Research (PTS). The stages of the method are: (1) Planning; (2) Implementation; (3) Reflection; and (4) Observations. After the implementation of supervision on the analysis of high school accreditation instruments / MA to the teachers of target schools in Sambas District through the supervision of individuals and groups. Results obtained: (1) There was an increase in teacher ability in making APP in the even semester for the annual program from 77.2% to 83.2% increased by 6.0%, semester programs from 75% to 82.3% increased 7.3%, syllabus from 70.7% to 84.1% increased 13.4%, RPP from 66.8% to 74.6% increased 7.8% and KKM from 37.5% to 75.0% increased 37.5%; and (2) The average value of teacher ability in making APP from 65.4% to 79.8% with an increase of 14.4%.